(untitled) (Journal of Asian Development Studies, 2017)
The present study is an attempt to analyze the role of government size for economic growth. A panel of selected South Asian Developing countries is used for analysis. Data from 1990 to 2016 is used for empirical investigation. Panel cointegartion is used for the analysis. The results indicated that there is a non linear relationship between the size of the government and economic growth. The study confirms the existence of ARMEY CURVE relationship in the selected panel.